Jehovas Zeugen in Polen 1945-1989: die Verfolgungsgeschichte einer religiösen Minderheit - Slupina, Wolfram ca. 21. Jh. (Kirchliche Zeitgeschichte, 2002)
It is not generally known that the J.Ws in Poland were persecuted by the communist authorities for about 40 years, or that 16000 of them were sentenced to lengthy terms of imprisonment. This record can be divided into five periods: from 1945-1950 there were popular demonstrations against J. Ws which led to at least 60 deaths, and on 2 July 1950 to a total prohibition of the sect by the state. From 1950-1956 there followed the first severe wave of persecution with mass arrests and brutal interrogations. At least 16 and possibly 18 persons were murdered. The cause was principally an unwillingness to accept the J.Ws' Christian neutrality, and a suspicion that they had contacts in non-socialist countries abroad. From 1956-7 the so-called Gomulka era brought a thaw and even an amnesty. But from 1957-1977 a second wave of repression set in, together with a campaign of internal disruption, whose object was to impose surveillance by the state, and a splintering of the religious community. In this connection, co-operation took place between the Polish secret police (UB) and the corresponding agency (Stasi) in the former East Germany. Between 1977 and 1989 a second thaw took place when it became possible to have visits from American and other international representatives of the Witnesses, and even to organize large-scale international congresses. Even so, the government — in vain — attempted to maintain its censorship. Finally on 12 May 1989 the legally-binding registration of the Witnesses was completed. There are now some 175000 members, making it the third largest religious community in Poland.